Mind Mapping to Improve Critical Thinking Skills and Learning Achievement of Elementary School Student - Sari, Devy Rusmia; Handoyo, Eko; Awalya, Awalya (Journal of Primary Education, 2020)
This research aims to find out differences of critical thinking skill and learning achievement among students taught by using mind mapping activitis. This quasi experimental research used non-equivalent control group design. The sample consisted of 50 students from 2 Primary Schools in Jati, Kudus district. Experimental class with 25 students were implementation problem based learning with mind mapping and Control class with 25 students used conventional learning with mind mapping. The data collection used was performance test. The techniques of analysing data were requirement using variance and N-gain tests. The findings showed that problem based learning model and mind mapping activities could improve critical thinking skill and learning achievement of student. The critical thinking skills in problem based learning classs obtained better than that of the convention class as well as than learning achievements. Based on the results of the study it can be concluded that problem based learning model by using mind mapping could improve critical thinking skill and social study learning achievement of student.